Validitas Modul IPA dengan Model Pembelajaran IPA Berbasis Kolaborasi untuk Meningkatkan Keterampilan Berpikir Kritis dan Keterampilan Mengambil Keputusan - Muhammad Aditya Saputra; Sutarto Hadi; Arif Sholahuddin; Ai Sulastri; Muhammad Hasbie; Mohamad Nor Aufa; Muhammad Awaluddin Fitri (Jurnal Penelitian Pendidikan IPA, 2023)
Students in schools use techniques to keep up with the increasingly rapid development of the times. A module is the learning media. Lessons will be easier for students to understand if teaching materials are simple, practical, and relevant. However, activity in living things is still regarded as unsuitable learning material. This is because presenting the characteristics of objects to students in real terms can also be challenging. As a consequence, research and development of teaching materials for class VIII SMP/MTs based on critical thinking and decision-making skills are carried out in motion modules on living things. The goal of this research and development is to validate SMP/MTs class modules in order to improve critical thinking and decision-making skills. The Tessmer Formative evaluation development model is used in this type of research. Aspects of validity include content, presentation, and language. The research data were analyzed descriptively into categories. The results show that the CBSL module developed is in a very valid category with a value of 3.51, implying that this module appears to follow the objectives of learning science and is technically very feasible to be used as a science learning resource.